Simulation with arena - Kelton, W David; Sadowski, Randall P; Sadowski, Deborah A (Boston : Mcgrawhill Publications, 1998)
Simulation with Arena is a comprehensive guide to using the Arena software for discrete event simulation. It provides a practical approach to learning simulation modeling and analysis, using real-world examples to illustrate key concepts and techniques. The book covers fundamentals of simulation, Arena software, model building, data collection and analysis, and output analysis. Designed for students and professionals in industrial engineering and business departments, this book is a valuable resource for anyone who wants to improve their decision-making processes through simulation.
Includes appendix, bibliographical references (p. 521-523) and index.
Keywords: Discrete event simulation; Computer simulation; Arena software